2002
DOI: 10.1034/j.1600-0722.2002.11193.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience of pain during an orthodontic procedure

Abstract: This study investigated pain experiences during a common orthodontic treatment. Fifty-five patients (12-18 yr) starting treatment due to crowding were included. Molar elastic separators were inserted bilaterally, and telephone interviews were made during evenings for a week. Pain intensity was assessed on a VAS scale, and pain medications were recorded. Forty-eight patients (87%) reported pain the first evening. The highest intensity of pain was reached the day after placement of separators (VAS mean = 43.7). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
199
3
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(222 citation statements)
references
References 30 publications
14
199
3
6
Order By: Relevance
“…4,5,[13][14][15][16][17] Earlier studies also showed that male patients have different expectations of orthodontic treatment than female patients. Although female patients seek treatment to improve their appearance and self-confidence, male patients want treatment to improve their social well-being.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[13][14][15][16][17] Earlier studies also showed that male patients have different expectations of orthodontic treatment than female patients. Although female patients seek treatment to improve their appearance and self-confidence, male patients want treatment to improve their social well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is no objective scale with which to measure the intensity of pain perceived, the VAS scale was chosen because it has been shown to be the most reliable and accurate tool in the evaluation of subjective experiences such as pain. 19,35 The experimental groups had been formed in such a way that there were an equal number of male and female patients in each group (Table 1). Care was taken that the patients with similar malocclusions and social background were selected.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the findings of other studies, 5,18 which have found the greatest need for analgesics to exist within 3 days after archwire placement. Bergius et al 19 found that 87% of participants reported pain on the first evening, but the most intense pain was reported to occur the day after archwire placement.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in local anaesthetics as well as its delivery armamentarium have resulted in painless extractions but the fear of post extraction pain deters many patients from undergoing this procedure [1][2][3][4][5][6]. Soft tissue trauma is one of the reasons for post extraction pain and various techniques have been tried to reduce this component's contribution.…”
Section: Introductionmentioning
confidence: 99%